Differences Between Founder-Led and Non-Founder-Led Congregations: A Research Note - Pitt, Richard N. (Review of religious research, 2020)
While sociologists have had a longstanding interest in religious leadership and congregational authority structures, most of the research in this area ignores the fact that many congregational leaders started the congregations they lead. Being in this unique position, founding pastor, likely gives them unusual authority to shape church policy and practice in, as yet, unexamined ways. Using three waves of the National Congregational Study, we examine differences between congregations led by their first (i.e., founding) pastor and congregations led by subsequent pastors hired by or assigned to those congregations. The paper concludes with a discussion of the implications of these differences.